National Identity as a General Principle of EU Law and its Impact on the Obligation to Recover State Aid - Marek Rzotkiewicz (Yearbook of Antitrust and Regulatory Studies, 2016)
Unlike other general principles of EU law, which derive from the CJ jurisprudence, the principle of national identity is based on a clear legal provision. Article 4(2) TEU stipulates that the Union shall respect important State functions, like the territorial integrity of the State, maintaining law and order and safeguarding national security. The list of values covered by the national principle identity is open and it is for the Member State to decide what values should be protected by its national identity, while the CJ is only empowered to determine the relevance of national identity under EU law. This article analyses if the principle of national identity could influence the EC examination of State aid and if the EC should refrain from issuing an order to recover incompatible aid, if that aid was to be protected by the Member State’s national identity. There has not yet been a single judgment by the CJ on that issue and the question stays open. The analysis also focuses on the division of competences between Member States and EU institutions in carrying out that analysis, as well as on the requirements for that analysis, including the scope of an examination carried out by EU institutions.